Glass reinforcing agent, reinforcing method for glass thinning process, and glass substrate
Patent Information
- Application Number
- CN202611444938.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]基于此,有必要提供玻璃补强剂、玻璃减薄工艺的补强方法以及玻璃基板,以解决玻璃蚀刻减薄后表面微观缺陷引起强度低的问题
[0028]该玻璃补强剂可以渗透至蚀刻减薄后玻璃表面的微观缺陷中,利用硅酸盐、硅烷偶联剂和水解调节剂的复配体系填充微观缺陷并实现固化交联增韧。其中硅酸盐水解形成的硅酸凝胶与硅烷偶联剂可以构架稳定的Si-O-Si三维交联网络,改善硅酸凝胶脆性,钝化裂纹尖端应力集中,实现BOR强度提升。同时,利用水解调节剂可以调控硅酸盐的水解速率,保证玻璃补强剂的渗透效果并避免析出沉淀物。因此,采用该玻璃补强剂对蚀刻减薄后玻璃进行处理后,不仅可以有效填充微观缺陷并提升强度,降低蚀刻减薄后玻璃在搬运和裁切等后续加工程序的碎片率,提升生产良率;而且玻璃的蚀刻速率并不会发生改变,完全兼容后续玻璃的加工处理。
Smart Images

Figure CN123003161A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of glass thinning technology, and in particular to glass reinforcing agents, reinforcing methods for glass thinning processes, and glass substrates. Background Technology
[0002] After the TFT (Thin Film Transistor) liquid crystal display glass substrate undergoes hydrofluoric acid chemical etching for thinning, numerous micron- and nanon-sized open-type microcracks, etching pits, and surface irregularities are formed on the glass surface and subsurface. These microscopic defects significantly reduce the BOR ring crush strength of the glass substrate, making it highly susceptible to edge chipping and breakage during subsequent cutting, cleaning, and module bonding processes. This results in a persistently high breakage rate, severely reducing product yield and increasing production costs.
[0003] Traditional techniques employ etching followed by polishing to eliminate these micro-defects. However, the polishing process easily creates new scratches and causes secondary damage, and it cannot correct the crack structure. Although high-temperature ion exchange can be used to repair micro-defects, the temperature of high-temperature ion exchange exceeds 400°C, which can burn out the TFT circuitry and damage the liquid crystal structure. Summary of the Invention
[0004] Therefore, it is necessary to provide glass reinforcing agents, reinforcement methods for glass thinning processes, and glass substrates to solve the problem of low strength caused by microscopic defects on the surface after glass etching and thinning.
[0005] In a first aspect, this application provides a glass reinforcing agent, the raw materials of which include silicates, silane coupling agents, hydrolysis modifiers, and solvents. The glass reinforcing agent contains silicates at a mass percentage of 2.0% to 4.5%, silane coupling agents at a mass percentage of 0.4% to 0.9%, and hydrolysis modifiers at a mass percentage of 0.08% to 0.15%.
[0006] In some embodiments, the glass reinforcing agent satisfies at least one of the following conditions:
[0007] (1) Silicates include at least one of sodium silicate, potassium silicate and lithium silicate;
[0008] (2) The silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane and vinyltriethoxysilane;
[0009] (3) The hydrolysis regulator includes at least one of acetic acid, formic acid and citric acid;
[0010] (4) The solvent includes at least one of water, ethanol and isopropanol;
[0011] (5) The pH value of the glass reinforcing agent is 9.0~10.5.
[0012] Secondly, this application also provides a reinforcement method for a glass thinning process, comprising the following steps:
[0013] The glass after etching and thinning is immersed in the glass reinforcing agent of the first aspect.
[0014] Then, the glass that has been soaked is cured.
[0015] In some embodiments, the immersion treatment is carried out at a temperature of 45°C to 60°C for a time of 8 min to 25 min.
[0016] In some embodiments, the curing temperature is 80°C to 90°C and the time is 10 min to 30 min.
[0017] In some implementations, the etching thinning process satisfies at least one of the following conditions:
[0018] (1) The etching solution used for etching and thinning contains 8% to 12% hydrofluoric acid by mass.
[0019] (2) The etching thinning process includes at least one etching process, and the thickness of the glass thinned by a single etching process is 0.1 mm to 0.2 mm;
[0020] (3) The glass thickness after etching and thinning treatment is 0.3mm~0.5mm.
[0021] In some embodiments, the reinforcement method further includes cleaning the glass after immersion treatment before the glass is cured.
[0022] In some embodiments, the reinforcement method further includes polishing at least one surface of the glass before etching to thin it.
[0023] Thirdly, this application also provides a glass substrate, which is prepared by the reinforcement method of the glass thinning process of the second aspect. The glass substrate includes glass and a silica gel cured material disposed in the micro-defects on the surface of the glass.
[0024] In some embodiments, the glass substrate satisfies at least one of the following conditions:
[0025] (1) The thickness of the glass substrate is 0.3mm~0.5mm;
[0026] (2) The Weber value of the BOR strength of the glass substrate is ≥300N.
[0027] Compared with traditional technologies, this application has at least the following beneficial effects:
[0028] This glass reinforcing agent can penetrate into the microscopic defects on the surface of etched and thinned glass. A composite system of silicates, silane coupling agents, and hydrolysis modifiers fills these defects and achieves curing, cross-linking, and toughening. The silica gel formed by silicate hydrolysis, combined with the silane coupling agent, constructs a stable Si-O-Si three-dimensional cross-linked network, improving the brittleness of the silica gel, passivating stress concentration at crack tips, and enhancing BOR strength. Simultaneously, the hydrolysis modifier regulates the silicate hydrolysis rate, ensuring the penetration effect of the glass reinforcing agent and preventing the precipitation of deposits. Therefore, treating etched and thinned glass with this glass reinforcing agent not only effectively fills microscopic defects and improves strength, reducing the breakage rate during subsequent processing such as handling and cutting, thus improving production yield, but also maintains the glass etching rate, ensuring complete compatibility with subsequent glass processing. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments and examples of this application, and to more completely understand this application and its beneficial effects, the accompanying drawings used in the description of the embodiments or examples will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of this application. Those skilled in the art can obtain other drawings based on these drawings without any creative effort.
[0030] Figure 1 This is a probability plot of the normal -95% confidence interval for the strength test in Embodiment 1 of this application;
[0031] Figure 2 This is a probability plot of the normal -95% confidence interval for the strength test in Embodiment 2 of this application;
[0032] Figure 3 This is a probability plot of the normal -95% confidence interval for the strength test in Example 3 of this application;
[0033] Figure 4 This is a probability plot of the normal -95% confidence interval for the strength test in Example 4 of this application;
[0034] Figure 5 This is a probability plot of the normal -95% confidence interval for the strength test of Comparative Example 1 of this application;
[0035] Figure 6 This is a probability plot of the normal -95% confidence interval for the strength test of Comparative Example 2 of this application;
[0036] Figure 7 This is a probability plot of the normal -95% confidence interval for the strength test of Comparative Example 3 of this application;
[0037] Figure 8 This is a probability plot of the normal -95% confidence interval for the strength test of Comparative Example 4 of this application;
[0038] Figure 9 This is a probability plot of the normal -95% confidence interval for the strength test of Comparative Example 5 of this application;
[0039] Figure 10 This is a probability plot of the normal -95% confidence interval for the strength test of Comparative Example 6 of this application;
[0040] Figure 11 This is a probability plot of the normal -95% confidence interval for the strength test of Example 7 of this application;
[0041] Figure 12 This is a diagram showing the fracture state of the glass substrate used for strength testing in Embodiment 1 of this application;
[0042] Figure 13 This is a diagram showing the fracture state of the glass substrate used in the strength test of Embodiment 4 of this application;
[0043] Figure 14 This is a diagram showing the fracture state of the glass substrate used in the strength test of Comparative Example 1 of this application.
[0044] Figure 15 This is a diagram showing the fracture state of the glass substrate used in the strength test of Comparative Example 2 of this application.
[0045] Figure 16 This is a diagram showing the fracture state of the glass substrate used in the strength test of Comparative Example 3 of this application.
[0046] Figure 17 This is a diagram showing the crack state of the glass substrate used in the strength test of Comparative Example 4 of this application. Detailed Implementation
[0047] The present application will be further described in detail below with reference to the embodiments and examples. These embodiments and examples are only for illustrating the present application and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to make the disclosure of the present application more thorough and comprehensive. It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various modifications or alterations without departing from the spirit of the present application, and the equivalent forms obtained also fall within the protection scope of the present application. In addition, numerous specific details are set forth in the following description to provide a fuller understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.
[0048] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.
[0049] In this application, the terms "first aspect," "second aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first aspect," "second aspect," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.
[0050] In this application, when numerical intervals (i.e., numerical ranges) are mentioned, unless otherwise specified, the distribution of selectable numerical values within the numerical interval is considered continuous, and includes the two endpoints of the numerical interval (i.e., the minimum and maximum values), as well as every numerical value between these two endpoints. Unless otherwise specified, when a numerical interval refers only to integers within that numerical interval, it includes the two endpoint integers of the numerical range, as well as every integer between the two endpoints, which is equivalent to directly listing every integer. When multiple numerical ranges are provided to describe features or characteristics, these numerical ranges can be merged. In other words, unless otherwise specified, the numerical ranges disclosed in this application should be understood to include any and all subranges included therein. The "numerical value" in the numerical interval can be any quantitative value, such as a number, percentage, ratio, etc. The term "numerical interval" can be broadly included to include percentage intervals, ratio intervals, proportion intervals, etc.
[0051] Traditional techniques employ mechanical polishing to treat etched and thinned glass, eliminating surface micro-defects caused by etching. However, the depth of etching-induced cracks is significant, and these defects may persist even after polishing. Furthermore, given the glass's thickness of only 0.4 mm after thinning, secondary scratches and fragmentation are easily generated during mechanical polishing. This application discovers that silicates such as sodium silicate can penetrate into the micro-defects of glass and hydrolyze to form silica gel, thus repairing and reinforcing these defects. However, the cured silica gel exhibits a loose and brittle structure, making it prone to shrinkage and cracking, resulting in poor strength stability of the reinforced glass. Further, this application achieves a synergistic effect by compounding a silane coupling agent with silicates and controlling the hydrolysis rate of the silicates using a hydrolysis regulator, thereby forming a stable cured silica gel within the micro-defects and effectively improving the strength of the etched and thinned glass.
[0052] The first aspect of this application provides a glass reinforcing agent, the raw materials of which include silicates, silane coupling agents, hydrolysis modifiers, and solvents.
[0053] The glass reinforcing agent contains silicates at a mass ratio of 2.0% to 4.5%, silane coupling agents at a mass ratio of 0.4% to 0.9%, and hydrolysis regulators at a mass ratio of 0.08% to 0.15%.
[0054] For example, the mass percentage of silicate in the glass reinforcing agent can be 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0%, 4.2%, 4.4%, or 4.5%. Selecting the above-mentioned mass percentage of silicate in the glass reinforcing agent allows the silicate to fully penetrate into the crack and hydrolyze to form silica gel, thereby fully filling the microscopic crack defects. If the mass percentage of silicate is relatively high, silica gel may easily precipitate and block the micropores on the glass surface, reducing the penetration effect.
[0055] For example, the mass percentage of silane coupling agent in a glass reinforcing agent can be 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, or 0.9%. Selecting the above mass percentages for the silane coupling agent in the glass reinforcing agent helps construct a Si-O-Si cross-linked network, improving the brittleness of the silica gel, enhancing its toughness, and inhibiting gel shrinkage and cracking. However, if the mass percentage of the silane coupling agent is relatively high, it may agglomerate, producing flocculent suspensions and reducing the reinforcing penetration effect.
[0056] For example, the mass percentage of hydrolysis regulator in the glass reinforcing agent can be 0.08%, 0.09%, 0.10%, 0.11%, 0.12%, 0.13%, 0.14%, or 0.15%. Selecting the mass percentage of hydrolysis regulator in the glass reinforcing agent as above can effectively regulate the hydrolysis rate of silicate and effectively prevent precipitation.
[0057] In some embodiments, the silicate includes at least one of sodium silicate, potassium silicate, and lithium silicate.
[0058] In some embodiments, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, and vinyltriethoxysilane.
[0059] In some embodiments, the hydrolysis regulator includes at least one of acetic acid, formic acid, and citric acid.
[0060] In some embodiments, the solvent includes at least one of water, ethanol, and isopropanol.
[0061] In some embodiments, the pH value of the glass reinforcing agent is 9.0 to 10.5, for example, it can be 9.0, 9.2, 9.4, 9.6, 9.8, 10.0, 10.2, 10.4, or 10.5. Controlling the pH of the glass reinforcing agent as described above ensures controlled hydrolysis of silicates and maintains moderate hydrolysis of the silane coupling agent. If the pH value is relatively high, the silicate hydrolysis rate may be too fast due to excessive alkalinity, causing premature precipitation of silicate gel, which cannot penetrate into the microcracks.
[0062] The second aspect of this application also provides a method for reinforcing a glass thinning process, comprising the following steps:
[0063] The glass after etching and thinning is immersed in the glass reinforcing agent of the first aspect.
[0064] Then, the glass that has been soaked is cured.
[0065] This reinforcement method employs a glass reinforcing agent immersion process, allowing the silicate and silane coupling agents in the reinforcing agent to penetrate into the microscopic defects on the glass surface. After curing, a stable silica gel solidifies, effectively improving the glass's strength. Furthermore, this reinforcement method utilizes relatively low processing temperatures, preventing damage to the TFT circuitry and liquid crystal layer. The process is simple and low-cost, effectively solving the problems of high temperatures and secondary damage caused by mechanical polishing in traditional high-temperature ion exchange methods.
[0066] In some embodiments, the immersion treatment temperature is 45°C to 60°C, for example, 45°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, 58°C, or 60°C. Controlling the immersion treatment temperature as described above can promote the penetration of silicate and silane coupling agents in the glass reinforcing agent into the micro-defects of the etched glass, further improving the reinforcing effect.
[0067] In some embodiments, the soaking time is 8 min to 25 min, for example, it can be 8 min, 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min or 25 min.
[0068] In some embodiments, the curing temperature is 80°C to 90°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C, or 90°C. Selecting the curing temperature as described above can promote cross-linking and curing of the silica gel in the micro-defects, further improving the reinforcement stability.
[0069] In some embodiments, the curing time is 10 min to 30 min, for example, it can be 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min or 30 min.
[0070] It should be noted that a suitable etching thinning method can be selected based on the desired glass thickness and performance requirements. For example, an etching solution containing hydrofluoric acid can be used to perform multiple etching processes on the glass to reduce it to a preset thickness.
[0071] In some embodiments, the etching solution used for etching thinning contains 8% to 12% hydrofluoric acid by mass, for example, 8.0%, 8.5%, 9.0%, 9.5%, 10.0%, 10.5%, 11.0%, 11.5%, or 12.0%.
[0072] In some embodiments, the etching thinning process includes at least one etching process. Optionally, the thickness reduction of the glass by a single etching process is 0.1 mm to 0.2 mm. It is understood that multiple etching processes can be performed using a double-sided spraying method during the etching thinning process.
[0073] In some embodiments, the glass thickness after etching and thinning is 0.3 mm to 0.5 mm.
[0074] Optionally, the etching and thinning process is carried out at a temperature of 30°C to 35°C.
[0075] Understandably, during the etching and thinning process, the etching solution can be circulated and agitated throughout to ensure uniform etching on both sides of the glass and significantly reduce deep pits and stress concentrations caused by local over-etching, thereby reducing the generation of micro-defects such as microcracks from the source.
[0076] In some embodiments, the glass after etching and thinning is washed with water to remove etching residues and residual etching solution formed on the surface.
[0077] In some embodiments, before curing the glass, the reinforcement method further includes cleaning the glass after immersion. By cleaning the glass after immersion in the glass reinforcing agent, residual glass reinforcing agent on the glass surface can be removed, and glass reinforcing agent retained in micro-defects can be avoided, thus preventing the formation of a continuous film layer on the substrate surface, improving the surface effect of the glass after curing, and avoiding the formation of appearances such as haze, watermarks, or interference patterns.
[0078] Optionally, the cleaning process includes rinsing the glass surface with water.
[0079] Optionally, the cleaning process takes 1 to 3 minutes.
[0080] In some embodiments, before etching to thin the glass, the reinforcement method further includes polishing at least one surface of the glass. Polishing the glass before etching to thin it removes surface particulate impurities and scratches, avoids uneven etching during the etching process, and further reduces the formation of micro-defects on the surface, thereby effectively improving the strength of the glass.
[0081] Optionally, the polishing pressure is 0.05MPa~0.15MPa, the polishing time is 15min~25min, and the polishing speed is 30Hz~50Hz.
[0082] Optionally, the polished glass can be cleaned, dusted, and dried to remove oil and dust from the polished surface. For example, the drying temperature can be 80°C to 100°C.
[0083] Exemplarily, a reinforcement method for a glass thinning process is provided, comprising the following steps:
[0084] After polishing at least one side of the glass, an etching solution is used to etch and thin the glass; wherein the etching and thinning process includes at least one etching process, and the thickness of the glass reduced by 0.1 mm to 0.2 mm by a single etching process.
[0085] The etched and thinned glass is immersed in a glass reinforcing agent at 45℃~60℃ for 8min~25min. The glass is then removed and cleaned. Finally, it is cured at 80℃~90℃ for 10min~30min.
[0086] The third aspect of this application also provides a glass substrate, which is prepared by the reinforcement method of the glass thinning process of the second aspect. The glass substrate includes glass and a silica gel cured material disposed in the micro-defects on the surface of the glass.
[0087] The glass substrate uses silane coupling agent and silicate in the glass reinforcing agent to cross-link and solidify in micro-defects to form silica gel solidified material, which can effectively repair micro-defects after glass thinning, improve the strength of the glass, and reduce the risk of breakage during glass processing after thinning.
[0088] In some embodiments, the thickness of the glass substrate is 0.3 mm to 0.5 mm.
[0089] In some embodiments, the Weber value of the BOR strength of the glass substrate is ≥300N.
[0090] The embodiments of this application will be described in detail below with reference to examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this application, or follow experimental manuals or conventional conditions in the art, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the art.
[0091] Example 1
[0092] S1. Polish both sides of a TFT glass substrate with a length × width of 1300mm × 1100mm and a thickness of 1mm. Then, clean with a cleaning agent for 10 minutes, rinse with water, and dry at 90℃. The polishing process uses a polishing slurry containing cerium oxide, with a polishing pressure of 0.1MPa, a polishing time of 20 minutes, and a polishing speed of 40Hz.
[0093] S2. Under an environment of 30℃, the TFT glass substrate treated in step S1 is etched and thinned using a double-sided spray segmented etching method to reduce the thickness of the TFT glass substrate to 0.4mm. During this process, the etching solution is circulated and agitated to ensure uniform etching. Then, the TFT glass substrate after etching and thinning is washed with water to remove surface residues and residual etching solution. The etching solution used is a 10% hydrofluoric acid aqueous solution, and the thickness removed in a single etching is 0.1mm.
[0094] S3. The TFT glass substrate treated in step S2 is immersed in a glass reinforcing agent at 50°C for 15 minutes to allow the glass reinforcing agent to penetrate into the microscopic defects on the surface of the TFT glass substrate. Then, it is rinsed with water for 2 minutes to remove any residual glass reinforcing agent from the glass surface. The glass reinforcing agent contains 3.5% sodium silicate, 0.6% γ-aminopropyltriethoxysilane, 0.12% acetic acid, and the remainder water, with a pH of 9.8.
[0095] S4. The TFT glass substrate processed in step S3 is cured at 85°C for 20 minutes to obtain the TFT glass substrate.
[0096] Example 2
[0097] The TFT glass substrate was prepared according to the method of Example 1, except that in step S3, the glass reinforcing agent contained sodium silicate with a mass ratio of 2.0%, γ-aminopropyltriethoxysilane with a mass ratio of 0.4%, acetic acid with a mass ratio of 0.08%, and the balance water with a pH value of 9.2.
[0098] Example 3
[0099] The TFT glass substrate was prepared according to the method of Example 1, except that in step S3, the glass reinforcing agent contained sodium silicate with a mass ratio of 4.5%, γ-aminopropyltriethoxysilane with a mass ratio of 0.9%, acetic acid with a mass ratio of 0.15%, and the balance water with a pH value of 10.3.
[0100] Example 4
[0101] The TFT glass substrate was prepared according to the method of Example 1, except that step S1 was omitted and the TFT glass substrate was directly etched and thinned.
[0102] Comparative Example 1
[0103] S1. A TFT glass substrate with a length × width of 1300mm × 1100mm and a thickness of 1mm is provided. The TFT glass substrate is etched and thinned to 0.4mm using a double-sided spray segmented etching method at 30℃. During the etching process, the etching solution is circulated and agitated to ensure uniform etching. The TFT glass substrate after etching and thinning is then washed with water to remove surface residue and residual etching solution. The etching solution used is a 10% hydrofluoric acid aqueous solution, and the thickness removed in a single etching pass is 0.1mm.
[0104] S2. Polish both sides of the TFT glass substrate after step S1. Then clean with a cleaning agent for 10 minutes, rinse with water, and dry at 90°C. The polishing process uses a polishing slurry containing cerium oxide, with a polishing pressure of 0.1 MPa, a polishing time of 20 minutes, and a polishing speed of 40 Hz.
[0105] S3. The TFT glass substrate processed in step S2 is cured at 85°C for 20 minutes to obtain the TFT glass substrate.
[0106] Comparative Example 2
[0107] The TFT glass substrate was prepared according to the method of Example 1, except that the mass percentage of sodium silicate in the glass reinforcing agent in step S3 was 3.5%, and the remainder was water.
[0108] Comparative Example 3
[0109] The TFT glass substrate was prepared according to the method of Example 1, except that the mass percentage of γ-aminopropyltriethoxysilane in the glass reinforcing agent in step S3 was 0.6%, and the remainder was water.
[0110] Comparative Example 4
[0111] The TFT glass substrate was prepared according to the method of Example 1, except that the mass percentage of sodium silicate in the glass reinforcing agent in step S3 was 5.0%, and the remainder was water.
[0112] Comparative Example 5
[0113] The TFT glass substrate was prepared according to the method of Example 1, except that in step S3, the glass reinforcing agent contained sodium silicate with a mass ratio of 3.5%, γ-aminopropyltriethoxysilane with a mass ratio of 0.6%, and the remainder water.
[0114] Comparative Example 6
[0115] The TFT glass substrate was prepared according to the method of Example 1, except that in step S3, the glass reinforcing agent contained 0.6% γ-aminopropyltriethoxysilane, 0.12% acetic acid, and the remainder water.
[0116] Comparative Example 7
[0117] The TFT glass substrate was prepared according to the method of Example 1, except that in step S3, the glass reinforcing agent contained sodium silicate with a mass ratio of 3.5%, acetic acid with a mass ratio of 0.12%, and the remainder water.
[0118] The TFT glass substrates prepared in the above embodiments and comparative examples were subjected to strength tests, including the following steps:
[0119] Fifty TFT glass substrates were used as test samples. Under conditions of 25°C and 101.3 MPa, the TFT glass substrates were placed on a BOR ring. The upper support ring of the BOR ring had a diameter of 38 mm, the spherical diameter was 127 mm, and the outer diameter of the support dimension was 68 mm. The ratio of the upper support ring diameter to the outer diameter of the support dimension was 0.559. A dual-servo floor-standing tensile testing machine (model HXK2103-20) was used to uniformly load the TFT glass substrates and the BOR at a rate of 5 mm / min until the TFT glass substrates fractured. The fracture state was observed, and the maximum load value was recorded. The maximum load values of the 50 TFT glass substrates were processed to obtain the 95% confidence interval Weber values and the average value of the maximum load values, which were recorded as the BOR strength. The probability plots for Examples 1-4 and Comparative Examples 1-7 are shown below. Figure 1-11 As shown in the figure. The test results are shown in Table 1.
[0120] Table 1
[0121]
[0122] As can be seen from the table above:
[0123] As can be seen from Examples 1-3, the TFT glass substrates of Examples 1-3 have essentially no defects on their surface, and both the BOR strength and the 95% confidence region Weber value are greater than 300N. After strength testing, as shown... Figure 12 The glass shown exhibits regular fracture patterns and no divergent cracks on the surface after crushing. Its dense cross-linked structure makes it suitable for ultra-thin display substrates with fewer micro-defects and high appearance requirements.
[0124] Compared to Example 4, Example 4 did not polish the glass before etching and thinning, resulting in numerous defects in the glass itself before etching, leading to more microscopic defects on the etched glass surface. However, after repair with a glass reinforcing agent, the surface defects were significantly reduced compared to traditional glass substrates, and the BOR strength and 95% confidence region Weber value were both greater than 300N. Figure 13 It can be seen that the fragments in Example 4 remain well-formed after being broken.
[0125] Compared to Comparative Example 1, Example 1, using a traditional processing method, resulted in more micro-scratches on the glass substrate surface, and all micro-cracks were in an open state, leading to significant stress concentration. (Combined with...) Figure 14 It can be seen that after the test, the cracks in the glass substrate of Comparative Example 1 are dendritic, and the BOR strength and the Weber value in the 95% confidence zone are both below 300N.
[0126] Compared to Comparative Example 2, Example 1 only used sodium silicate for glass reinforcement by soaking. The resulting silica gel structure was loose and brittle, easily shrinking and cracking after drying. Although it showed some strength improvement compared to Comparative Example 1, the BOR strength and 95% confidence zone Weber value were still below 300 N. Figure 15 It can be seen that the glass substrate of Comparative Example 2 still exhibits a tree-like divergence after it is cracked.
[0127] Compared to Comparative Example 3, Example 1 only used a silane coupling agent to soak the glass. The silane coupling agent only slightly modified the glass surface and could not fill and repair micro-defects. Stress concentration patterns still existed, and the BOR strength and 95% confidence region Weber value were still below 300 N. Combined with… Figure 16 It can be seen that the glass substrate of Comparative Example 3 still exhibits a tree-like divergence after it is cracked.
[0128] Compared to Comparative Example 4, Example 1, which used a high concentration of sodium silicate to soak the glass, still showed no significant improvement in performance. Figure 17 It can be seen that after the glass substrate of Comparative Example 4 cracked, it still exhibited a dendritic pattern, and both the BOR strength and the 95% confidence zone Weber value were still below 300N.
[0129] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0130] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these modifications and improvements all fall within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the appended claims, and the specification can be used to interpret the content of the claims.
Claims
1. A glass reinforcing agent, characterized in that, The raw materials of the glass reinforcing agent include silicates, silane coupling agents, hydrolysis regulators, and solvents; wherein the mass percentage of the silicates in the glass reinforcing agent is 2.0% to 4.5%, the mass percentage of the silane coupling agent is 0.4% to 0.9%, and the mass percentage of the hydrolysis regulator is 0.08% to 0.15%.
2. The glass reinforcing agent as described in claim 1, characterized in that, The glass reinforcing agent satisfies at least one of the following conditions: (1) The silicate includes at least one of sodium silicate, potassium silicate and lithium silicate; (2) The silane coupling agent includes at least one of γ-aminopropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane and vinyltriethoxysilane; (3) The hydrolysis regulator includes at least one of acetic acid, formic acid and citric acid; (4) The solvent includes at least one of water, ethanol and isopropanol; (5) The pH value of the glass reinforcing agent is 9.0~10.
5.
3. A reinforcement method for a glass thinning process, characterized in that, Includes the following steps: The glass after etching and thinning is immersed in the glass reinforcing agent described in claim 1 or 2. The glass after immersion is then cured.
4. The reinforcement method for the glass thinning process as described in claim 3, characterized in that, The soaking treatment is performed at a temperature of 45℃ to 60℃ for a time of 8 min to 25 min.
5. The reinforcement method for the glass thinning process as described in claim 3, characterized in that, The curing process is carried out at a temperature of 80℃~90℃ for a time of 10min~30min.
6. The reinforcement method for the glass thinning process as described in claim 3, characterized in that, The etching thinning process satisfies at least one of the following conditions: (1) The etching solution used in the etching and thinning process contains 8% to 12% hydrofluoric acid by mass. (2) The etching thinning process includes at least one etching process, and the thickness of the glass thinned by a single etching process is 0.1 mm to 0.2 mm; (3) The thickness of the glass after etching and thinning treatment is 0.3mm-0.5mm.
7. The reinforcement method for the glass thinning process as described in any one of claims 3-6, characterized in that, Before the glass is cured, the reinforcement method further includes cleaning the glass after the immersion treatment.
8. The reinforcement method for the glass thinning process as described in any one of claims 3-6, characterized in that, Before etching and thinning the glass, the reinforcement method further includes polishing at least one side surface of the glass.
9. A glass substrate, characterized in that, The glass substrate is prepared by the reinforcement method of the glass thinning process according to any one of claims 3-8, and the glass substrate includes glass and a silica gel cured material disposed in the micro-defects on the surface of the glass.
10. The glass substrate as claimed in claim 9, characterized in that, The glass substrate satisfies at least one of the following conditions: (1) The thickness of the glass substrate is 0.3mm~0.5mm; (2) The Weber value of the BOR strength of the glass substrate is ≥300N.